2012
DOI: 10.1038/ejhg.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

The role of renin–angiotensin–aldosterone system polymorphisms in phenotypic expression of MYBPC3-related hypertrophic cardiomyopathy

Abstract: The phenotypic variability of hypertrophic cardiomyopathy (HCM) in patients with identical pathogenic mutations suggests additional modifiers. In view of the regulatory role in cardiac function, blood pressure, and electrolyte homeostasis, polymorphisms in the renin-angiotensin-aldosterone system (RAAS) are candidates for modifying phenotypic expression. In order to investigate whether RAAS polymorphisms modulate HCM phenotype, we selected a large cohort of carriers of one of the three functionally equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
0
19
1
2
Order By: Relevance
“…Однако в другом исследовании, проведенном Kolder IC [13] у 368 паци-ентов с ГКМП, носителей мутаций MYBPC, такой ассо-циации не получено. Имеются сведения об ассоциации полиморфизма А166С гена AGTR1 с развитием гипертрофии ЛЖ [14]. А. Osterop et al [15] изучали роль полиморфизма AGTR1 в развитии гипертрофии ЛЖ у 104 пациентов с ГКМП.…”
Section: Discussionunclassified
“…Однако в другом исследовании, проведенном Kolder IC [13] у 368 паци-ентов с ГКМП, носителей мутаций MYBPC, такой ассо-циации не получено. Имеются сведения об ассоциации полиморфизма А166С гена AGTR1 с развитием гипертрофии ЛЖ [14]. А. Osterop et al [15] изучали роль полиморфизма AGTR1 в развитии гипертрофии ЛЖ у 104 пациентов с ГКМП.…”
Section: Discussionunclassified
“…As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress (Berezin, 2016e), genotype of guanine nucleotide-binding proteins (G-proteins) beta-3 subunit (GNB3) (Fazakas et al, 2016), transcription factor Islet-1 gene (McNamara et al, 2014), troponin T (Friedrich et al, 2013), CYP2D6 polymorphism (Hofman et al, 2010), cardiac myosin binding protein-C mutations (Friedrich et al, 2013), renin-angiotensin-aldosterone system polymorphism (Sutter et al, 2013) etc. Indeed, it is well known that angiotensin-converting enzyme (ACE) I/D gene D allele was associated with higher overall mortality as compared with the I allele in HF patients and that the effect could be modified by ACE inhibitors' given (Kolder et al, 2012). Additionally, ACE DD and angiotensin-1-receptor 1166 CC genotypes may synergistically increase the predisposition to HFpEF (Wu et al, 2010).…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…In this context, the novel risk scores reflecting variabilities in genetic and epigenetic features in HF development appear to be promised (Berezin, 2016c;Lopes and Elliott, 2013;Yang et al, 2015). Indeed, (Berezin, 2016d;Fazakas et al, 2016;Friedrich et al, 2013;Hofman et al, 2010;Kolder et al, 2012;McNamara et al, 2014;Sutter et al, 2013). As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress (Berezin, 2016e), genotype of guanine nucleotide-binding proteins (G-proteins) beta-3 subunit (GNB3) (Fazakas et al, 2016), transcription factor Islet-1 gene (McNamara et al, 2014), troponin T (Friedrich et al, 2013), CYP2D6 polymorphism (Hofman et al, 2010), cardiac myosin binding protein-C mutations (Friedrich et al, 2013), renin-angiotensin-aldosterone system polymorphism (Sutter et al, 2013) etc.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Indeed, some early studies have reported interested results with respect to genetic precursors of HFpEF and HFrEF [16][17][18][19][20][21][22]. As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress [16], genotype of guanine nucleotide-binding proteins (G-proteins) β-3 subunit (GNB3) [17], transcription factor Islet-1 gene [18], troponin T [19], CYP2D6 polymorphism [20], cardiac myosin binding protein-C mutations [19], renin-angiotensin-aldosterone system polymorphism [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress [16], genotype of guanine nucleotide-binding proteins (G-proteins) β-3 subunit (GNB3) [17], transcription factor Islet-1 gene [18], troponin T [19], CYP2D6 polymorphism [20], cardiac myosin binding protein-C mutations [19], renin-angiotensin-aldosterone system polymorphism [21] etc. Indeed, it is well known that angiotensin-converting enzyme (ACE) I/D gene D allele was associated with higher overall mortality as compared with the I allele in HF patients and that the effect could be modified by ACE inhibitors' given [22].…”
Section: Introductionmentioning
confidence: 99%